Kinerja Protokol Greedy Perimeter Stateless Routing Protokol (GPSR) Menggunakan Roadside Unit (RSU) Pada Vehicle Ad-Hoc Network (VANET) di Area Kota Malang - Ragil Setyo Utomo; Primantara Hari Trisnawan; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Vehicular ad-hoc network (VANET) is a wireless network technology that allow vehivle can communicate with ohter vehicle. VANET have 3 way to communicate, that is vehicle to vehicle communication (V2V), infrastructure to vehicle (I2V) or (V2I), and infrastructure to infrastructure (I2I). This study focused at the distance placement in each road side unit (RSU). This study focused at the distance placement in each road side unit (RSU). Communication in VANET, its need good performance in sending data from vechile to vehicle for communication between vehicle to vehicle as well as vehicle to RSU or the other round can be delivered faster and the percentage of success information arrived is increasing. In this study protocol greedy perimeter stateless routing (GPSR) will be implement with RSU to know which distant in each RSU is better to implement. Implementation will be worked with Network Simulator (NS-2) and SUMO. The result from this implementation will be analyzed with test parameters that is throughput, end-to-end delay, and packet delivery ratio. From the result based on vehicle density, RSU with distant 300 m have better value, that is 1570 bps and 85,7143% compared from RSU with distance 400 m, that is 1530 bps and 500m with value 1520 bps. And also the value of packet delivery ratio for RSU with 400 m is 77,7778% and 500 m with 75%. However on implemention result based on vehicle speed, RSU with 400 distance 400 m have same performance with RSU distance 300 m. In other word, RSU placement with distance is taking effect toward routing performance.